2022
DOI: 10.3389/fpsyt.2022.826277
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Psychological and Behavioral Consequences of Self-Isolation During Lockdown: A Longitudinal Study Across United Kingdom and Italy

Abstract: IntroductionSeveral countries imposed nationwide or partial lockdowns to limit the spread of COVID-19 and avoid overwhelming hospitals and intensive care units. Lockdown may involve restriction of movement, stay-at-home orders and self-isolation, which may have dramatic consequences on mental health. Recent studies demonstrated that the negative impact of lockdown restrictions depends on a wide range of psychological and socio-demographic factors.AimsThis longitudinal study aimed to understand how internal fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…In Lee et al's study [135], a greater frequency of dog walking was significantly associated with better health for both caregivers and dogs, and there was an indirect effect of dog walking on loneliness, partially mediated by attachment to the dog. However, Lau and Oliva [133] found that dog-walking was not associated with loneliness or mindfulness, and Zaninotto et al [194] found that dog-walking was associated with fewer negative psychological symptoms in caregivers during the last (fourth) week of their lockdown study only.…”
Section: Factors Relating To Animalsmentioning
confidence: 98%
“…In Lee et al's study [135], a greater frequency of dog walking was significantly associated with better health for both caregivers and dogs, and there was an indirect effect of dog walking on loneliness, partially mediated by attachment to the dog. However, Lau and Oliva [133] found that dog-walking was not associated with loneliness or mindfulness, and Zaninotto et al [194] found that dog-walking was associated with fewer negative psychological symptoms in caregivers during the last (fourth) week of their lockdown study only.…”
Section: Factors Relating To Animalsmentioning
confidence: 98%
“… Amodu and Ama (2016) proposed reflected modeling to explain the above phenomenon: with the increase of external pressure, individuals will be exposed to the role model of social entrepreneurship orientation, such as external stakeholders, and then reflect on the value of parents as the role model of social entrepreneurship orientation ( Ramus and Killmer, 2010 ). Therefore, the development of social entrepreneurship orientation results from individual integration of various role models of social entrepreneurship orientation ( Kraus et al, 2017 ; Zaninotto et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%